Memory benefits of daily-living-related contextual cueing for individuals with subjective cognitive decline and mild cognitive impairment - Chien-hsiou Liu; Kuan-yi Li; Wan-wen Liao; I-ching Chuang; Yan-hua Huang; Ching-yi Wu (SAGE Publishing, 2024)
Objective We aimed to assess how daily-living-related contextual cueing (DLCC) affects memory performance in three groups: healthy older adults (HA), those with subjective cognitive decline (SCD), and mild cognitive impairment (MCI), while accounting for age and education. Methods After gathering demographic information, participants underwent neuropsychological assessments including the Montreal Cognitive Assessment (MoCA), Everyday Cognition Scale (ECog-12), Mini Mental State Examination (MMSE), Geriatric Depression Scale (GDS), and Trail Making Test (TMT) to establish baseline characteristics. Participants were categorized into HA ( N = 47), SCD ( N = 54), and MCI ( N = 43) groups based on MoCA and ECog-12 scores. Memory performance was evaluated through two components of the Contextual Memory Test (CMT): one with non-contextual cues and the other with daily-living-related contextual cues. Results Interaction effects between contextual cueing and group for immediate recall ( p < .001), delayed recall ( p < .001), and total recall ( p < .001) were found. All recall scores were lower in the MCI group than in the other two groups in the contextual cueing, not non-contextual. The post-hoc results revealed that scores on immediate recall, delayed recall, and total recall were lower in the MCI group than in the other two groups in the contextual cueing condition but not in the non-contextual cueing one. Conclusions Daily-living-related contextual cueing benefited HA, SCD, and younger-adult MCI groups more than older-adult MCI group, particularly enhancing delayed and total memory performance.